An Unusual Presentation of B-Cell Lymphoma as a Large Isolated Epiglottic Mass: Case Report and Literature Review - Changxing Liu; Sean Delaney; Tamara N. Brown (Case Reports in Otolaryngology)
Extranodal presentation of B-cell lymphoma is uncommon. Isolated primary epiglottic B-cell lymphoma is even rarer. To our knowledge, there has been only one description of isolated B-cell lymphoma presenting as a large epiglottic mass. We report an unusual type of B-cell lymphoma of the epiglottis, as it could not be subtyped based on routine staining and hybridization. The lymphoma presented as a large isolated globular mass pedicled to the epiglottis, occupying most of the oropharynx, but did not have any ball-valving effect or increased respiratory efforts. Initial radiographic findings were nonspecific. The diagnosis of B-cell lymphoma was determined by transoral incisional biopsy under local anesthesia. The condition was treated successfully with chemoradiation. The current standard of treatment for high grade B-cell lymphoma is concurrent chemoradiotherapy, with excellent prognosis. Although rare, B-cell lymphoma should be considered when investigating pedunculated hypopharyngeal masses.